GAMBARAN KADAR ASAM URAT PADA WANITA MENOPAUSE DI PANTI SOSIAL TRESNA WERDHA ILOMATA KECAMATAN SIPATANA KOTA GORONTALO TAHUN 2019 (Journal of Health, Technology and Science (JHTS), 2020)
Uric Acid is the final product of purine metabolism. Uric acid in the hu-man body is produced by the body (endogenous uric acid) and comes from food (exogenous uric acid). About 80-85% of uric acid is produced by the body, while the rest comes from food, which can trigger uric acid in women who are postmenopause due to a decrease in the hormone estrogen which can not produce normal estrogen hormones and also because of factors from a lot of food contain purines. The purpose of this study was to determine levels of uric acid in menopause women, distribution of uric acid levels, a history of gout in menopause women.This research is a descriptive quantitative research approach. The ins-pection method used is spectrophotometry. The sampling technique in total sampling with a total sample of 26 respondents group of elderly menopause women.The results of a study conducted on 26 respondents based on the distri-bution of uric acid levels obtained as many as 21 with a percentage (80.8%) of respondents who are not normal and as many as 5 respondents with a percentage (19.2%) declared normal, whereas based on the distribution of diet there are 5 respondents in the percentage (19.2%) were low purine and 21 respondents with a percentage (80.8%) high purine. Conclusion as many as 21 respondents who experienced abnormal uric acid because respondents consume foods that are high in purines.
Keywords: Gout, Menopause Women